An analysis of the semantic of the Term “الرجوع” in the Quran - Saheed Adewale Mikail (Indonesian Journal of Arabic Studies, 2024)
Purpose– This study aims to examine the Qur’ānic vocabulary denoting the concept of “return” and to analyze it in light of the theory of semantic fields, in order to reveal its lexical and semantic characteristics, its contextual relationship within the Qur’ān, and the subtle distinctions in meaning between seemingly synonymous expressions. The research seeks to demonstrate how the Qur’ān employs these expressions with remarkable precision, reflecting the depth of its semantic structure, in which no word can be replaced by another without altering the intended meaning. Design/methods/approach – The researcher employed an inductive and analytical method by tracing all Qur’ānic words that convey the notion of “return.” Data were collected through the Ayat database developed by King Saud University and Al-Ma‘ānī Al-Jāmi‘ Dictionary. The identified words were then classified into two categories: those with concrete meanings of return and those with abstract or metaphorical meanings. The analysis was enriched by the views of classical exegetes and linguists as well as previous semantic studies addressing synonymy and inter-lexical relations in the Qur’ān. Findings – The findings reveal that Qur’ānic words of return display a wide range of semantic variations between literal and figurative meanings. Some words, such as atā (أتى), acquire additional connotations through contextual usage, while others, like tāba (تاب), retain their original sense related to repentance and turning toward truth. The study concludes that the relationship among these words does not reflect absolute synonymy but rather partial synonymy governed by rhetorical precision and contextual particularity. Research implications – The research contributes to a deeper semantic understanding of Qur’ānic language and highlights the decisive role of context in meaning determination. It opens new avenues for linguistic and Qur’ānic studies and provides a refined linguistic approach to interpreting religious texts from both semantic and linguistic perspectives.